Andean sponges reveal long-term benthic ecosystem shifts following the end-Triassic mass extinction - Ritterbush, Kathleen A.; Rosas, Silvia; Corsetti, Frank A.; Bottjer, David J.; West, A. Joshua (Palaeogeography, palaeoclimatology, palaeoecology, 2015)
Thick cherts and cherty dolomites in the basal Jurassic Aramachay Formation of Peru preserve a thriving continental shelf community dominated by siliceous sponges that followed the end-Triassic collapse of metazoan-rich carbonate accumulation. Similar Hettangian and Sineumurian deposits from Nevada, U.S.A., Austria, and Morocco suggest that an Early Jurassic siliceous sponge takeover was a widespread phenomenon that persisted for ~2m.y. until metazoan-driven carbonate sedimentation recovered. The post-extinction dominance of siliceous sponges likely resulted from the confluence of metazoan carbonate reef collapse (removal of incumbents) and geochemical conditions that fostered the success of the siliceous sponge-dominated ecosystem. Simple mass balance calculations suggest the siliceous sponge takeover was likely permitted by an increased silica flux as a consequence of weathering Central Atlantic Magmatic Province (CAMP) basalts. The CAMP basalts alone could supply all the silica needed to sustain the sponge takeover, although contributions were also likely from increased hot-climate weathering of other silicates and possible reductions in dissolved silica demand by radiolarians. Detailed sedimentological, fossil, and microfacies analyses were conducted at six field sites across a shallow shelf system recorded in the central Peruvian Andes (Yauli Dome), focusing on the metazoan contribution to sedimentation. Sedimentary structures at all six sites demonstrated on-shelf deposition, similar to the underlying upper Triassic Chambará Formation (in contrast to the black shale-rich facies of the Aramachay Formation in other areas of Peru). Examination of up to 147m of cherty dolomite from the Aramachay Formation revealed a siliceous sponge-dominated ecosystem, including sponge body fossils, compressed in situ sponge materials, and abundant transported spiculite sediments. Siliceous sponges, mostly demosponges and rare hexactinellids, account for the chert lithology and apparently dominated the local ecology for approximately two million years. The role of metazoan biocalcifiers in sediment production and ecological structure was profoundly reduced compared to the under- and overlying formations, representing a clear ecological state shift from pre-extinction carbonate to post-extinction siliceous dominated ecosystems before the carbonate system recovered ~2m.y. after the extinction. •We examine post-extinction paleoecology in the Aramachay Formation (Central Peru).•Widespread cherts record ecologically dominant siliceous demosponges.•Level bottom inner to mid ramp demosponge sedimentation lasted approx. 2 Myr.•Contemporaneous records from Nevada (USA) and Austria share key features.•Calculations compare sponge Si demand with rapid increases from basalt weathering.